Outcome of surgery for traumatic cataract in children in a child eye health tertiary facility, Ibadan, Nigeria - Mary Ogbenyi Ugalahi; Bolutife Ayokunnu Olusanya; Olanipekun Olalekan Aremu; Aderonke Mojisola Baiyeroju (Therapeutic Advances in Ophthalmology, 2021)
Objective: The objective of this study was to describe the outcome of surgery for traumatic cataract and associated factors in children aged 16 years and below operated in a tertiary facility. Methods: This was a retrospective review of records of children who had surgery for traumatic cataract between August 2015 and August 2019. Information on biodata, preoperative visual acuity, surgical methods, complications, and postoperative visual acuity were retrieved. Data were analyzed using IBM SPSS Statistics 20.0. Results: Traumatic cataract accounted for 87 (14.7%) of 593 eyes operated for childhood cataract during the period. Of these, a total of 79 records were available for review. There were 56 (70.9%) males with a mean age of 10.11 (±3.39) years. All injuries were unilateral; closed globe injuries accounted for 70 (88.8%) of the cataracts and the left eye was affected in 42 (53.2%) patients. Fifty-two (67.09%) eyes had other ocular injuries apart from cataracts. The morphology of the cataract was membranous in 44 (55.7%) eyes, and 76 (96.2%) eyes had cataract surgery with intraocular lens (IOL) implantation; 39 (51.3%) of these IOLs were implanted within the capsular bag. The preoperative best corrected visual acuity was worse than 6/18 in all 79 (100%) eyes and improved to 6/18 or better in 32 (40.5%) eyes at 3 months postoperatively. Conclusion: Traumatic cataract accounted for less than a quarter of all childhood cataracts in our center. Majority of the eyes had successful IOLs implantation during surgery, and the best corrected visual acuity improved in a moderate proportion of these patients.